Dampak Broken Home terhadap Perilaku Siswa - Niken Maharani; Amala Sari; Siti Amanah (Journal on Education, 2023)
The study was to see how the broken home family was affected by the behavior of students at the 17 st ebis. The study involves qualitative methods. The data-collection techniques used are observation, documentation and interviews. Studies have found four of a number of students from a broken home home behaving (cranial, sb, am and ls). This is reflected in the admirable qualities of greeting, helping friends, and obeying school rules. As for one of the other broken home family students. This is reflected in some traits like habits that come late to school, make noises during study, are not used to saying hello at the meeting of teachers, disturb friends and habitually break school rules. From this explanation, researchers concluded that broken home had little effect on the good and absence of student behavior.